Analisis Kebutuhan Dan Pengembangan Dimensi Kepribadian Manusia - Nikmatun Naziroh; Yunita Sari; Nurhidayah Nurhidayah; Febrina Melinda Putri (Al-Khair Journal : Management, Education, And Law, 2022)
Abstract: The dimension of human personality creates difficulties in achieving the fulfillment of needs and their development, because the socioeconomic level of the community is still poor, for the fulfillment of primary needs alone is still difficult among the community. This article uses a descriptive qualitative method, this paper aims to map the form of difficulty of meeting the needs and development of the dimensions of the human personality and analyze its causes. The results of the study show that this study shows that human needs include three categories, namely basic needs such as clothing, food, and housing, secondary/supporting needs, and luxury or modern needs. The human personality is the dynamic of a functional psychophysical organization of human beings that turns into a pattern of a specific behavior in the face of life, and the manifestation of personality is all the behavior of the human being himself. The human personality that can be developed is education, science, Islamic education, and character education. So that the human personality becomes a solution for the progress and development of personality in human life. So it can be suggested that if you want to be happy, then live according to your ability level, and develop your personality according to your dimensions.Keywords: Needs, Development, Dimensions, Human Personality Abstrak: Dimensi kepribadian manusia menciptakan kesulitan dalam capaian pemenuhan kebutuhan dan pengembangannya, dikarenakan tingkat social ekonomi masyarakat masih banyak yang miskin, untuk pemenuhan kebutuhan primer saja masih sulit di kalangan masyarakat. Artikel ini menggunakan metode kualitatif deskriptif, tulisan ini bertujuan untuk memetakan bentuk kesulitan memenuhi kebutuhan dan pengembangan dimensi kepribadian manusia dan menganalisis penyebabnya. Hasil studi menunjukkan bahwa Studi ini menunjukkan bahwa kebutuhan manusia meliputi tiga kategori yaitu kebutuhan dasar/ pokok seperti sandang, pangan dan papan, kebutuhan sekunder/ penunjang, dan kebutuhan mewah atau modern. Kepribadian manusia merupakan dinamika sebuah organisasi psikofisik fungsional manusia yang berubah menjadi pola tingka laku yang sepesifik dalam menghadapi kehidupan, dan manifestasi dari kepribadian adalah semua tingkah laku dari diri manusia itu sendiri. Kepribadian manusia yang dapat dikembangkan adalah pendidikan, ilmu pengetahuan, pendidikan Islam, pendidikan karakter. Sehingga kepribadian manusia menjadi solusi bagi kemajuan dan pengembangan kepribadian dalam kehidupan manusia. Sehingga dapat disarankan jika ingin bahagia, maka hiduplah sesuai tingkat kemampuan, dan kembangkanlah kepribadian sesuai dimensi yang dimiliki. Kata Kunci: Kebutuhan, Pengembangan, Dimensi, Kepribadian Manusia